Analysis Factor That Influence The Level Of Disability In Leprosy Patients In Kediri Leprosy Hospital - Kentarti, Rima; Indasah, Indasah; Koesnadi, Koesnadi (Journal for Research in Public Health, 2019)
Leprosy if not handled carefully can cause disability, and the situation becomes a barrier for leprosy. The aim of the study was to analyze the regularity of treatment with MDT, self-care factors, paramedic role factors and family role factors that influence the level of disability of leprosy patients in Kediri leprosy hospital. The design was Cross Sectional. The population was leprosy patients. The sample size is 107 respondents using Simple Random sampling technique. Independent variables are family roles, officer roles, treatment, and self-care. the dependent variable is the level of disability. Data was collected using a questionnaire, analyzed using logistic regression tests with α ≤ 0.05. The results showed that Self-care (p = 0.002) is more dominant than the regularity of MDT treatment (p = 0.031) to the level of hand disability. Self-care (p = 0,000) is more dominant than the regularity of MDT treatment (p = 0.006) to the level of leg defects in leprosy patients. The role of the family has more influence on the regularity of MDT treatment, the role of the officer has more influence on self-care, self-care affects hand and foot disability more while the regularity of MDT treatment.